The evaluation of the content of fibers in steel fiber reinforced structures and image analysis - Ďubek, Marek; Makýš, Peter; Ďubek, Silvia; Petro, Marek (Journal of Civil Engineering and Management, 2018)
The distribution of fiber orientation is an important factor in determining the mechanical properties of fiber-reinforced concrete. This study proposes a new image analysis technique for improving the evaluation accuracy of fiber orientation distribution in the sectional image of fibers reinforced concrete. The article is devoted to research the systematic evaluation of fiber-cuts through the image processing software. Mathematical representation of the final dispersal of fibers in steel fiber-reinforced concrete is incorporated into a programmed evaluation software. The software detects fibers and classified according to their axes of rotation angle and size of the identified ellipse detection area. Image processing algorithm and detecting fibers has been developed only for these research purposes. Detection area is randomly inserted via steel fiber reinforced concrete structure. The results show the average value of uniformity in the fiber-samples produced in the laboratory.